THE EFFECT OF THE USE OF SMART BOARD MEDIA ON THE LEARNING OUTCOMES OF PANCASILA EDUCATION IN GRADE 1 STUDENTS OF ELEMENTARY SCHOOL MUHAMMADIYAH 1 KEDUNGGALAR - Annisa Diahayu Novitasari; Novia Rahma Rista Utami; Budi Sasomo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The implementation of Pancasila education at the elementary school level requires media such as smart boards in the learning process to support the teaching and learning process more interestingly. The use of this learning media has a positive impact on the overall psychological development of children. This media not only serves as a visual or audio aid, but also an effective means of fostering interest in learning, increasing motivation, and facilitating the understanding of concepts that may be difficult to understand. The type of research used is using a quantitative approach with the Pre-Experimental Design type. The researcher used a One Group Pretest-Posttest Design research design where it was carried out in one class without a comparison class by using a pretest before being given treatment. With that, the results of the treatment can be known more accurately, because it can be compared with the situation before being given treatment. The results of this study in the use of smart board media on the learning outcomes of Pancasila Education for grade 1 students of SD Muhammadiyah 1 Kedunggalar have a significant influence, this is found in the results of the pretest getting an average score (mean) of 60.50, while the posttest gets an average score (mean) of 86.50